2021
DOI: 10.3389/fphar.2021.654714
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Strategy of Network Pharmacological Prediction and Experimental Validation Elucidate Possible Mechanism of Bu-Yang Herbs in Treating Postmenopausal Osteoporosis via ESR1

Abstract: Postmenopausal osteoporosis (PMOP) is a type of bone metabolism disease-related to estrogen deficiency with an increasing incidence. Traditional Chinese (TCM) has always been used and showed effectiveness in treating PMOP. In the current study, Bu-Yang herbs were considered to be the most frequently used and efficient TCM herbs in PMOP treatment. However, chemical and pharmacological profiles were not elucidated. Network pharmacology was conducted on representative Bu-Yang herbs (Yin-Yang-Huo. Du-Zhong, Bu-Gu-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…Based on network pharmacology analysis, the core compounds of TCM have made great contributions to the therapeutic effect of treating diseases (42). In the present study, we firstly discovered that the top active compounds in ZGBSF consist of quercetin, luteolin, kaempferol, baicalein, etc.…”
Section: Discussionmentioning
confidence: 81%
“…Based on network pharmacology analysis, the core compounds of TCM have made great contributions to the therapeutic effect of treating diseases (42). In the present study, we firstly discovered that the top active compounds in ZGBSF consist of quercetin, luteolin, kaempferol, baicalein, etc.…”
Section: Discussionmentioning
confidence: 81%
“…In the current study, the network pharmacology analysis method refers to the previous study. We followed the methods of [ 5 ]. The chemical components of TCM herbs of Radix Rehmanniae Preparata and liquorice were searched on TCMSP and SYMMAP databases [ 16 , 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…OP is characterized by bone mineral density (BMD) loss, bone microarchitecture degenerated, and risk of fracture upregulated [ 3 ]. It is well accepted that OP is led by an imbalance between bone formation and bone resorption [ 4 , 5 ]. First-line clinical therapies mainly focused on inhibition of excessive bone resorption activity and few drugs focusing on enhancing attenuated bone formation were developed.…”
Section: Introductionmentioning
confidence: 99%
“… 17 Similarly, with the help of network pharmacology, we predicted and verified the potential pharmacological mechanism of Bu-Yang herbs for postmenopausal osteoporosis via regulating the Wnt/β-catenin signaling pathway. 18 Therefore, all this evidence indicated that network pharmacology analysis may be a good tool for exploring the chemical compositions of LWDHD and its relationships with IVDD.…”
Section: Introductionmentioning
confidence: 94%